INFORMATION SYSTEM FOR ADMISSION OF STUDENT INTERNSHIP AT RRI MEDAN - Ika Devi Perwitasari; Rindiani Rindiani; Hendry Hendry (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
The Internship Acceptance Information System at RRI Medan is a platform designed to facilitate the process of accepting internship students at Radio Republik Indonesia (RRI) Medan. The purpose of this system is to increase efficiency and effectiveness in the process of accepting apprentice students and to strengthen the relationship between RRI Medan and the surrounding universities. This system offers several important features, including online registration, submission of files, and tracking of application status. Students who are interested in doing an internship at RRI Medan can access this system via a website or an easy-to-use mobile application. They can fill out the online registration form and upload the required files, such as CVs, grade transcripts, and letters of recommendation. After registration is complete, the system will process the application and provide notifications to students regarding the status of their application. Students can track the progress of their applications through this system, including information regarding interview schedules or other selection tests. If accepted, students will receive confirmation through this system and can continue with the internship preparation stage. This information system is built on a web basis.